DC ice‐melting and temperature variation of optical fibre for ice‐covered overhead ground wire. Issue 2 (1st February 2016) - Jiang, Xingliang; Meng, Zhigao; Zhang, Zhijin; Hu, Jianlin; Lei, Yuqing
Abstract : To prevent atmospheric ice on optical fibre composite overhead ground wire (OPGW) from affecting the safe and stable operation of power system, applying the direct current (DC) ice‐melting technology to remove ice from OPGW is a feasible option. If the selection of DC ice‐melting current is unreasonable, the temperature of optical fibre can be extremely high which may shorten its operating life or even cause it to burn. Therefore, based on the finite element method, the ice‐melting process of OPGW under glaze icing condition is simulated by COMSOL and MATLAB. The ice‐melting time and temperature variations of optical fibre for ice‐covered OPGW under different environmental conditions are obtained. Then, a series of ice‐melting tests are carried out in an artificial climate chamber to verify the calculation results. Results show that the ice‐melting and temperature increase of optical fibre gradually slow down during the entire DC ice‐melting process. When ice sheds from the OPGW, the temperature of optical fibre reaches its maximum value. The ice‐melting time is closely related to the ice‐melting current, ambient temperature, wind speed, ice thickness and type of OPGW. The maximum temperature of optical fibre is significantly influenced by ice thickness and ice‐melting current.